An analytical solution of a finite domain convection-diffusion model for chloride intrusion into RC seawall. (January 2022) - Chen, Deqiang; Ni, Pengpeng; Li, Yuliang; Mei, Guoxiong; Xiao, Liang; Feng, Jianxue
Abstract: A reinforced concrete (RC) seawall experiences two-side attacks of chloride in seawater and salinized soil, including diffusion attack and seepage attack. In this view, a convection-diffusion model for RC seawall is proposed, taking into account the diffusion action, seepage action and binding of chloride. The analytical solution is derived by using the finite Fourier sine transform, and is further calibrated against the results calculated from the finite difference method (FDM). From the distribution of chloride in a RC seawall, it is found that the RC seawall near the seawater is more prone to corrosion. Then, the influence of different parameters on the chloride invasion in RC seawall is analyzed systematically. Results show that the influence of concrete parameters is the greatest, while that of soil parameters is the least. Moreover, based on the analytical solution, an anti-seepage technique is proposed to prevent chloride from invading into RC structures, the effectiveness of which is demonstrated by laboratory test results .